Aplikasi Sistem Keamanan Rumah Berbasis Internet Of Things Dengan Menggunakan Raspberry PI - Muhammad Makmun Effendi; Hengki Anthony Juliyanto (Jurnal SIGMA, 2021)
In this research discusses how to implement a home security system using internet technology so that the state of the house can be monitored remotely. The purpose of this research is to design a tool that is able to provide notifications and can be used as a remote monitoring tool by utilizing Internet of Things (IoT) technology and Telegram Bot as a notification receiver. By utilizing the HCSR501 infrared motion sensor, magnetic door switch, Picamera and Usb camera and Telegram Bot which is controlled using raspberry pi B + models using the Python programming language, a tool that is able to provide notifications can be made and can be made a home security monitoring tool. The tool can send notifications in the form of text messages and portrait pictures of Picamera and can be used as a monitoring tool by utilizing a browser to stream. Keyworad:Internet of Things (IoT), Telegram Bot, Security System, Raspberry Pi, Sensor PIR, Magnetic Door Switch, Picamera, USB Camera